A Study of Physical and Mechanical Properties: Durian Peel Starch-Sago Starch Biocomposite Bioplastic with Sorbitol Plasticizer Reinforced by Chitosan and Zinc Oxide - Rahmatullah Rahmatullah; Rizka Wulandari Putri; Rifqi Sufra; Muhammad Faiz Musyafa (Agroindustrial Technology Journal, 2025)
Conventional plastics causes various problems, particularly related to the environment and health. Their impacts include air and soil pollution, blocked airways leading to flooding, and disruption to marine and terrestrial ecosystems. Furthermore, non-biodegradable plastic bags can release hazardous chemicals and microplastics, which pollute the environment. To solve these problems, many researchers are developing environmentally friendly plastics made from biomass by combining various additives according to the plastic's function, commonly referred to as bioplastic biocomposites. Biocomposite bioplastic can be made from biomass raw materials such as starch. Durian peel waste contains not only cellulose but also quite high starch content. However, starch-based biocomposites have problems, especially in their mechanical properties. The use of fillers as reinforcements such as chitosan and ZnO is needed to overcome this problem. This study aims to determine the effect of adding fillers (chitosan and ZnO) to starch-based biocomposite bioplastic (durian peel and sago). The method used in making plastic biocomposites is mixing process and solution casting. Sorbitol plasticizer of 25% and fillers of 4% each for chitosan and ZnO were added for variations in the total starch of durian peel and sago (1.25:3; 2.25:3; 3:3). Based on the results of the durian peel flour composition, it is proven that it has a fairly high starch content of 68.67%. The results of physical/mechanical tests of the best biocomposite bioplastic were obtained in sample A with a tensile strength of 18.816 MPa, elongation of 1.422% and young's modulus of 13.05%. The addition of ZnO filler only affects thickness, tensile strength, and elongation. These results indicate that the combination of materials can improve the mechanical properties of bioplastics based on durian peel waste starch and sago starch.